The bottom line : balance sheets and P&Ls - Hayward, Nick; Collins, Cath; Video Education Australasia (Australia : Video Education Australasia, 2006)
Business owners rely on accounting reports to show how a business is performing. This program focuses on 2 of these reports, the balance sheet and profit and loss account or statement
Title from title screen
Voice over: Amy Blackmur
DVD format
Keywords: Financial statements